The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1413-82712011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Construção e estudos psicométricos de uma Escala de Avaliação da Impulsividade

Abstract: ResumoO trabalho teve como objetivo descrever a construção e os estudos psicométricos iniciais de uma escala para avaliação da impulsividade. Para isso foram realizados três estudos com três amostras diferentes de alunos de um curso técnico em segurança pública do estado de Minas Gerais. Em todos os casos, a análise da estrutura interna evidenciou a existência de quatro fatores. A denominação dos fatores foi "Falta de concentração e de persistência", "Controle cognitivo", "Planejamento futuro" e "Audácia e tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The items that comprise factor 3 did not achieve the criterion for unidimensionality. However, it should be considered that, (a) the data presented by Ávila-Batista and Rueda (2011) and Rueda and Ávila-Batista (2013) suggest the consistency of this set of items, and (b) despite surpassing that expected in the eigenvalues criterion, it can be considered that 2.2 is only marginally higher than 2. To verify whether these results occurred at random, ten databases were simulated (SIFILE = function) for each factor, with residuals being found that varied between 1.3 and 1.5 for factor 1 and between 1.3 and 1.9 for factor 3.…”
Section: Resultsmentioning
confidence: 85%
“…The items that comprise factor 3 did not achieve the criterion for unidimensionality. However, it should be considered that, (a) the data presented by Ávila-Batista and Rueda (2011) and Rueda and Ávila-Batista (2013) suggest the consistency of this set of items, and (b) despite surpassing that expected in the eigenvalues criterion, it can be considered that 2.2 is only marginally higher than 2. To verify whether these results occurred at random, ten databases were simulated (SIFILE = function) for each factor, with residuals being found that varied between 1.3 and 1.5 for factor 1 and between 1.3 and 1.9 for factor 3.…”
Section: Resultsmentioning
confidence: 85%
“…Next, the agents responded to the ESAVI (Impulsivity Assessment Scale) developed by Ávila-Batista (2011). Impulsivity is a complex construct that refers to hasty, unplanned behaviors with often detrimental consequences for individuals' lives.…”
Section: Methodsmentioning
confidence: 99%